The status of an illegitimate child in Islamic law: a critical analysis of DNA paternity test - Haneef, Sayed Sikandar Shah (Berkeley Electronic Press, 2016)
The use of DNA test to determine the paternity of a child is a controversial issue in Islamic law. Although vast majority of legal scholars pragmatically concede its use as ameans of connecting unidentifiable children or dead bodies to their next of kin, they oppose its use to ascribe the paternity of children born out of illicit sexual intercourse to the male parties involved. Consequently, such an illegitimate child is a liability on the female partner in terms of raising and supporting. The conventional logic for such a lopsided application of child’s paternity was that in the case of female partner, it is easy to ascertain that such a child is her biological progeny but establishing such a de facto connection of the child to hermale partner is impossible to obtain. Accordingly, practical option for the naïve even curious but sexually active female member to thwart the stigma and burden of giving birth to such children, has been either abortion or baby dumping (Statistics show that there were 417 baby dumping cases recorded nationwide between 2009 and September 2013. See more at: http://www.theantdaily.com/Main/Baby-dumping-cases-turn ing-into-an-epidemic-in-Malaysia#sthash.fpHHoWGk.dpuf.). This paper, however, argues that in the age of scientific technology invoking the conventional wisdom of non-traceability of male partner in a sexual act no longer holds true. Accordingly, biologically connecting ill-conceived babies to male partners, in the context of present Muslim societies, goes a long way in protecting women and children.